PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, STRUKTUR ASET, RISIKO BISNIS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Ari Tanjung Noor, 15.05.52.0292; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the effect of profitability, company size, asset structure, business risk and sales growth on the capital structure of real estate and property companies in 2013-2017. The population in this study are all successive real estate and property companies listed on the Indonesia Stock Exchange for the period 2013-2017. The sample selection uses a purposive sampling method. The analytical tool used in this study is multiple linear regression analysis. The test results show that profitability has a not significant effect on capital structure. Firm size has a significant positive effect on capital structure. The asset structure has not significant effect on capital structure. Business risk does not have a significant effect on capital structure. Sales growth has significant positive effect on capital structure.